Hakikat dan Fungsi Lembaga Pendidikan Islam dalam Membentuk Insan Kamil: Perspektif Filsafat Pendidikan Islam - Yahya Fadhlullah Murtaja; Ratna Ayu Fitriana; Hanifa Anan; Rustam Ibrahim (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This study aims to analyze the nature and function of Islamic educational institutions in shaping insan kamil from the perspective of Islamic educational philosophy. This research is motivated by the gap between the ideal objectives of Islamic education, which emphasize the formation of a complete human being, and the reality of educational practices that tend to focus on cognitive aspects and pragmatic needs. This study employs a qualitative approach with a library research method by analyzing relevant classical and contemporary literature. The results show that the essence of Islamic educational institutions lies in their role as a means of developing human potential in an integrated manner, encompassing intellectual, spiritual, and moral dimensions. Islamic educational institutions function not only as a medium for the transmission of knowledge but also as a vehicle for value internalization and character formation. The concept of insan kamil becomes the primary orientation, requiring a balance between intellect, spirit, and physical aspects. However, in practice, there is still a reduction in the function of Islamic educational institutions, which tend to prioritize academic achievement alone. Therefore, a reconstruction of philosophical understanding is necessary so that Islamic educational institutions can optimally perform their role in shaping holistic human beings. This study provides a conceptual contribution in strengthening the philosophical foundation of Islamic education and serves as a critical reflection for its development in the modern era.